2008
DOI: 10.1103/physrevd.77.126015
|View full text |Cite
|
Sign up to set email alerts
|

Fiber bundles and matrix models

Abstract: We investigate relationship between a gauge theory on a principal bundle and that on its base space. In the case where the principal bundle is itself a group manifold, we also study relations of those gauge theories with a matrix model obtained by dimensionally reducing them to zero dimensions. First, we develop the dimensional reduction of YangMills (YM) on the total space to YM-higgs on the base space for a general principal bundle. Second, we show a relationship that YM on an SU (2) bundle is equivalent to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
103
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 50 publications
2
103
0
Order By: Relevance
“…To check the validity of the formulation, some one-loop perturbative calculations were performed in [12]. It was shown that the tadpole vanishes and that the fermion one-loop self-energy agrees with the one in the continuum theory.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To check the validity of the formulation, some one-loop perturbative calculations were performed in [12]. It was shown that the tadpole vanishes and that the fermion one-loop self-energy agrees with the one in the continuum theory.…”
Section: Introductionmentioning
confidence: 99%
“…In [12], a non-perturbative formulation of N = 4 SYM on R × S 3 in the planar ('t Hooft) limit was proposed by using the plane wave matrix model (PWMM) [13] (for earlier discussions, see [14,15]). Note that N = 4 SYM on R 4 at a conformal point has the P SU(2, 2|4) symmetry with thirty-two supercharges and is equivalent to N = 4 SYM on R × S 3 through the conformal mapping.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations